Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Simplify: (4x^5)(-7x^5y^3)
A: (4x^5)(-7x^5y^3) = -28x^10 y^3
Get an answer
Original conversation
User: Simplify: (4x^5)(-7x^5y^3)

Weegy: Are you sure the question is written exactly that way?
Expert answered|Darkiedark|Points 83|

Question
Asked 9/3/2010 3:47:25 PM
Updated 8/27/2016 8:07:23 AM
1 Answer/Comment
This conversation has been flagged as incorrect.
Flagged by yeswey [6/3/2014 4:55:04 AM], Edited by Andrew. [8/27/2016 8:07:23 AM]
New answers
Rating
3
(4x^5)(-7x^5y^3) = -28x^10 y^3
Added 6/3/2014 4:54:59 AM
This answer has been confirmed as correct and helpful.
Confirmed by Andrew. [8/27/2016 8:07:24 AM]
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
What is a fused sentence
Question
Expert Answered
Updated 1/4/2015 8:41:34 AM
1 Answer/Comment
A fused sentence, also called a run-on, occurs when a writer has connected two main clauses with no punctuation.
Added 1/4/2015 8:40:41 AM
This answer has been confirmed as correct and helpful.
Confirmed by selymi [1/4/2015 8:41:36 AM]
Solve: 4 - 9x = 29 - 4x
Weegy: I'm sorry, i'm not good in math. (More)
Question
Expert Answered
Updated 2/26/2014 7:58:11 PM
1 Answer/Comment
4 - 9x = 29 - 4x

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5
Added 2/26/2014 7:58:11 PM
This answer has been confirmed as correct and helpful.
Solve for x: 4 - 9x = 29 - 4x
Weegy: 4 - 9x = 29 - 4x, -9x + 4x = 29 - 4, -5x = 25, x = 25/-5, x = -5 User: Solve for x: 13 + 5x = 22 + 8x Weegy: 13 + 5x = 22 + 8x, 5x - 8x = 22 - 13, -3x = 9, x = 9/-3, x = -3 (More)
Question
Expert Answered
Updated 2/26/2014 8:00:08 PM
0 Answers/Comments
Solve. 5x + 5 (x - 3) = 15
Weegy: x=3 (which would make it 15 + 0 = 15) (More)
Question
Expert Answered
Updated 196 days ago|12/9/2017 5:04:01 AM
1 Answer/Comment
5x + 5 (x - 3) = 15 ;

5x + 5x - 15 = 15 ;

10x = 15 + 15 = 30 ;

x = 30/10 = 3

Added 196 days ago|12/8/2017 2:41:44 PM
This answer has been confirmed as correct and helpful.
Confirmed by Masamune [12/9/2017 5:04:05 AM]
Solve. 10 - 5 (x - 5) = 4 (x - 1)
Weegy: x= 39/9 (More)
Question
Expert Answered
Updated 6/17/2014 5:31:04 AM
1 Answer/Comment
10 - 5 (x - 5) = 4 (x - 1)

10 - 5x + 25 = 4x - 4

-5x -4x = -4 - 10 - 25

-9x = -39

x = -39/-9

x = 13/3
Added 6/17/2014 5:31:04 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [6/17/2014 6:50:53 AM]
27,012,231 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 256 [Total 274] Ratings 0 Comments 186 Invitations 7 Offline
S
L
R
Points 145 [Total 296] Ratings 1 Comments 5 Invitations 13 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.